The ResQCPR System: An Objective and Systematic Review - Goodwin, D.O., EMT-P, RN-BSN, Glenn; Zeid, D.O., Tarik; Belok, D.O., Todd (International Journal of Innovative Research in Medical Science, 2021)
The resource-limiting environment of the pre-hospital setting necessitates the continuous development of tools and interventions that maximise the capabilities of emergency medical services (EMS) municipalities. One such product developed by Zoll, the ResQCPR system, attempts to enhance the effectiveness of prehospital cardiopulmonary resuscitation (CPR). The ResQCPR system is comprised of the ResQPOD, which is an impedance threshold device (ITD), and the ResQPUMP, which is an assisted compression-decompression (ACD) device. Limited data exists regarding Zoll’s specific apparatuses as well as similar such devices. This systematic analysis comprehensively summarises a number of related studies. Their methods, limitations, results, and other aspects are outlined in the respective sections. Conclusion: This review concludes by determining that the effectiveness of the ResQPUMP, in particular (and ACD devices in general), is promising while the ResQPOD’s is uncertain. Future studies are needed to determine whether the effectiveness of the ResQPUMP markedly diminishes when used independently of the ResQPOD. This is an important feature for fire departments and other EMS municipalities because outfitting all appropriate units with both devices can be quite costly. Further studies are also needed to demonstrate reproducibility in humans (because 2 of the studies used pigs as test subjects) and with a greater amount of test subjects.